Scope of the Two-Step, One-Pot Palladium-Catalyzed Borylation/Suzuki Cross-Coupling Reaction Utilizing Bis-Boronic Acid - Molander, Gary A. (2012)
The use of bis-boronic acid for the direct synthesis of boronic acids has greatly facilitated the two-step, one-pot borylation/Suzuki cross-coupling reaction between aryl- and heteroaryl halides. Making use of Buchwald’s second generation XPhos preformed catalyst, high yields of cross-coupled products were obtained for most substrates. The method also allows an efficient two-step, one-pot synthesis, providing access to three distinct cross-coupled products after column chromatography. The method also provides a rapid and convenient route to teraryl compounds.